Intraphase Microstructure–Understanding the Impact on Organic Solar Cell Performance. (16th May 2013) - Scholes, Fiona H.; Ehlig, Tino; James, Michael; Lee, Kwan H.; Duffy, Noel; Scully, Andrew D.; Singh, T. Birenda; Winzenberg, Kevin N.; Kemppinen, Pete; Watkins, Scott E.
Abstract A comprehensive study of the effect of intraphase microstructure on organic photovoltaic (OPV) device performance is undertaken. Utilizing a bilayer device architecture, a small molecule donor (TIPS‐DBC) is deposited by both spin‐coating and by thermal evaporation in vacuum. The devices are then completed by thermal evaporation of C60, an exciton blocking layer and the cathode. This bilayer approach enables a direct comparison of device performance for donor layers in which the same material exhibits subtle differences in microstructure. The electrical performance is shown to differ considerably for the two devices. The bulk and interfacial properties of the donor layers are compared by examination with photoelectron spectroscopy in air (PESA), optical absorption spectroscopy, charge extraction of photo‐generated charge carriers by linearly increasing voltage (photo‐CELIV), time‐resolved photoluminescence measurements, X‐ray reflectometry (XR), and analysis of dark current behavior. The observed differences in device performance are shown to be influenced by changes to energy levels and charge transport properties resulting from differences in the microstructure of the donor layers. Importantly, this work demonstrates that in addition to the donor/acceptor microstructure, the intraphase microstructure can influence critical parameters and can therefore have a significant impact on OPV performance.